Pricing for Profitability: Activity-Based Pricing for Competitive Advantage - John L. Daly (USA John Wiley & Sons, Inc., 2002)
Three things can happen when establishing a product price. A price set too high is a lost sale that could have been profitable at a lower price. A price set too low is rewarded with unprofitable work. Only when a price is set appropriately does a company make both a sale and a profit. Just as activity-based costing and activity-based management revolutionized the cost accounting world, activity-based pricing will bring a disciplined approach to developing pricing. Activity-based pricing examines the relationships between price, cost and sales volume and how this relationship effects profitability. Pricing for Profitability joins the disciplines of marketing, economics, business strategy, engineering and cost accounting to achieve maximum profitability.
Keywords: Accounting; Nonfiction; Business; Economics; Pricing